2018
DOI: 10.1002/ceas.12097
|View full text |Cite
|
Sign up to set email alerts
|

Counselor Trainees' Experiences Counseling Disability: A Phenomenological Study

Abstract: Transcendental phenomenology was used in this study to examine the lived experiences of counseling interns (N = 10) receiving multicultural training to assist clients with disabilities. Five essential themes were identified. Drawing on their findings, the authors recommend programmatic and curricular changes, including the infusion of personal narratives and service learning, to the multicultural training of counselors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…Additionally, participants in the current study reported, on average, the highest level of competency in self-awareness (M = 87.52), followed by self-perceived knowledge (M = 79.01) and self-perceived skills (M = 69.01). These results also lend support to previous findings of both Hollimon (2007;self-awareness M = 88.86, knowledge M = 78.53, and skills M = 68.05) and Strike (2001;self-awareness M = 88.63, knowledge M = 80.56, and skills M = 73.41), and they are consistent with the assertion that the self-awareness and knowledge domains of multicultural competence tend to be emphasized more than the skills domain within multicultural training (Priester et al, 2008). The lower level of competence associated with self-perceived skills may be partially related to the fact that practical experiences with IWDs are not often required in counselor training (Milsom & Akos, 2003) or to frequent errors made regarding case conceptualizations of clients with disabilities (Kemp & Mallinckrodt, 1996).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Additionally, participants in the current study reported, on average, the highest level of competency in self-awareness (M = 87.52), followed by self-perceived knowledge (M = 79.01) and self-perceived skills (M = 69.01). These results also lend support to previous findings of both Hollimon (2007;self-awareness M = 88.86, knowledge M = 78.53, and skills M = 68.05) and Strike (2001;self-awareness M = 88.63, knowledge M = 80.56, and skills M = 73.41), and they are consistent with the assertion that the self-awareness and knowledge domains of multicultural competence tend to be emphasized more than the skills domain within multicultural training (Priester et al, 2008). The lower level of competence associated with self-perceived skills may be partially related to the fact that practical experiences with IWDs are not often required in counselor training (Milsom & Akos, 2003) or to frequent errors made regarding case conceptualizations of clients with disabilities (Kemp & Mallinckrodt, 1996).…”
Section: Discussionsupporting
confidence: 71%
“…Nonetheless, these results seem to indicate greater coverage than was reported by Feather and Carlson (2019), who found that 50% of counselor educators indicated they integrate disability content into multicultural coursework. In general, results suggest that some progress may have been made since Priester et al (2008) reported that only 25% of syllabi for introduction to multicultural counseling courses mentioned the topic of disability.…”
Section: Discussionmentioning
confidence: 92%
“…Unfortunately, disability is absent in mainstream counseling literature, and multicultural counseling training overlooks PWD (Foley‐Nicpon & Lee, 2012; Rivas & Hill, 2018). Therefore, counselors who have unintentionally internalized society's prejudicial perspective toward disability may not have a chance to process their own biases throughout their counseling training and in professional life.…”
Section: Implications For Counseling Practicementioning
confidence: 99%
“…In one study, colorism did not influence students' clinical decisions as anticipated (Hairston, Laux, O'Hara, Roseman, & Gore, 2018); Hutchison et al (2018) presented a thematic analysis regarding knowledge and perceptions of cultural display rules in counseling practice. Qualitative researchers attended to students' experiences with psychodynamic theory and practice (Smith, 2018), metaphors in internship reflections (Storlie, Giegerich, Stoner-Harris, & Byrd, 2018), and interns' experiences related to disability-focused practice (Rivas & Hill, 2018).…”
Section: Understanding Stakeholdersmentioning
confidence: 99%